PERLINDUNGAN HUKUM TERHADAP DOSEN PERGURUAN TINGGI SWASTA YANG DI-PHK - Johannes Mangapul Turnip; Budiman Ginting; Jusmadi Sikumbang; Agusmidah Agusmidah (Universitas Sumatera Utara, 2018)
ABSTRACT Legal bond between faculty and Colleges formally lead to the employment relationship which in exercising its rights and obligations are subject to the terms agreed work. The working relationship is always formulated in employment contracts that briefly load work requirements, rights and obligations. In accordance with Article 45 and Article 46 of the Law on Teachers and Lecturers, professors are required to have academic qualifications, competence, teaching certificate, physically and mentally healthy, and meet other qualifications required units of higher education places on duty, as well as having the ability to achieve national education goals. Research shows that the Treaty System work done by Colleges and faculty can be a Certain Time Employment Agreement (PKWT) and Time-specific Employment Agreement (PKWTT). The agreement made would give rise to different implications including the rights that will be received as severance pay if the employment agreement the lecturer is based on a work agreement for an unspecified time (PKWTT) and if the employment agreement is based on a work agreement specific time (PKWT) the reimbursement loss shall be granted by the wage / labor until the time of expiry of the employment agreement. Against the validity of the employment contract Lecturer What Not Meet Minimum Academic Qualification in accordance with Law on Teachers and Lecturers can be said to be invalid, because the Law on Teachers and Lecturers already set the terms in accordance with the Minimum Academic Qualification to become a lecturer / faculty. These requirements must be met in order to improve the quality of lecturers / lecturers such. Consideration judges hear the case in the Supreme Court of Appeals No. 048 PK / Pdt.Sus / 2010 is in conformity with the rules in the Labor Law. Consideration of the judge in the decision likening faculty with labor / worker and dispute resolution refers to the settlement of labor disputes. Keywords: Legal Protection, Lecturer Colleges, layoffs